Aplikasi pupuk organik vermikompos sebagai komposisi media tanam pada pertumbuhan bibit kelapa sawit di pre-nursery - Rina Ekawati; Alfatah Hidayat Romadhoni (AGROLOGIA: Jurnal Ilmu Budidaya Tanaman, 2023)
The research was conducted with the aim of identifying the response of organic fertilizer vermicompost as a composition of planting media in pre-nursery on the growth of oil palm seedlings. This research was conducted in Teaching Farm Wedomartani, Ngemplak, Sleman Regency, Yogyakarta from April to June 2022. This study implemented a randomized block design with a single factor. The composition of the planting media as a factor that consisted of five treatments, namely: subsoil (100%), subsoil (80%) + vermicompost (20%), subsoil (70%) + vermicompost (30%), subsoil (60%) + vermicompost (40%), and subsoil (50%) + vermicompost (50%). Each treatment was repeated three times. The results showed that the application of vermicompost as planting media composition in the pre-nursery with subsoil gave the oil palm seedlings higher growth than the control (without vermicompost). The application of subsoil with vermicompost gave the plant height, number of leaves, stem diameter, and wet and dry plant weight higher than the control. Application of subsoil (80%) + vermicompost (20%) produced the best plant height, number of leaves, stem diameter, and wet and dry weight of oil palm seedlings.